Mutu Fisikokimia dan Sensori Keripik Jamur Tiram (Pleurotus ostreatus) serta Biaya Produksinya - Namirah, Aisyah Maryam; Sugiyono, Sugiyono; Adawiyah, Dede Robiatul (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
The increased consumption of oyster mushrooms in Indonesia faces challenges due to their short shelf life, which makes it difficult to sell them in fresh form. One of the solutions is to process them into oyster mushroom chips, which offer a longer shelf life and appeal as a snack product. This study aimed to evaluate oyster mushroom chips' physicochemical and sensory qualities and calculate their production costs. The research was conducted in two stages. In the first stage, oyster mushroom chips were produced by applying a pretreatment to the fresh oyster mushrooms (blanching and rinsing), and coating them using different flours (wheat flour and a mixture of wheat and rice flour). The resulting oyster mushroom chips were analyzed for their sensory quality. In the second stage, the chips were produced using the best treat-ment identified in the first stage, followed by frying at different temperatures (150 °C or 155 °C). The resulting chips were analyzed for physicochemical and sensory quality, and their production cost was calcu-lated. The results of the first stage showed that the combination of rinsing and wheat flour coating produced chips that were significantly preferred by the panelists for taste, aroma, and texture attributes. The second stage showed that there were no significant sensory quality differences between chips fried at 150 °C or 155 °C. However, the frying temperature caused significant differences in the fat, protein, carbohydrate, crude fiber content, and total energy of the chips. The production cost of the oyster mushroom chips was Rp 31,748 per 250 g package.